Results of a 5-year contraceptive trial in parous and nulliparous women with a new LNG-IUS. (4th March 2017) - Wildemeersch, Dirk; Goldstuck, Norman D; Jackers, Geert
Abstract: Objective : To report on the contraceptive performance and continuation of a new T-shaped LNG-IUS, releasing 20 μg of levonorgestrel/day, in both parous and nulliparous nulliparous women after 5 years of use. Materials and methods : An observational prospective contraceptive study conducted in parous and nulliparous women up to 48 years of age. Results : The study was conducted in a sample size of 356 women of whom 67.1% were parous and 32.9% were nulliparous with mean age of 35.1 (range 15–48). The total cumulative observation period was 27 269 woman-months. Only one accidental pregnancy was observed and two expulsions were reported with no partial expulsions. There were 12.7% medical removals for abnormal bleeding, pain and other medical reasons, mostly not related to the use of the LNG-IUS, and 13.3% removals in women wishing to become pregnant. The discontinuation rate at 5 years amounts to 25.7% including women with pregnancy wish, who used the LNG-IUS for an average of 44 months. There were no serious adverse events (e.g. perforation, pelvic inflammatory disease). Conclusion : The LNG-IUS used in this study is highly effective and well tolerated resulting in a high continuation of use. The only two expulsions that occurred during the study is remarkable. The ease and safety of insertion together with optimal retention is considered an advance in intrauterine contraceptive device technology.